(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The research affirmed that Cola nitida L. and Garcinia kola Heckel used in Nigeria are quite different medicinally and nutritionally. The proportions of all nutrients analyzed quantitatively (lipid, moisture, fibre, ash, and protein except carbohydrate) were greater in C. nitida than in G. kola Heckel (p<0.05). C. nitida has a lower energy density than G. kola Heckel (332.20 kcal/g vs 349.10 kcal/g sample) (p<0.05). Alkaloids, flavonoids, phenolics, and cardiac glycosides were all significantly greater in G. kola Heckel than C. nitida at p<0.05, in addition to saponin, tannin, and steroids. A 72-hour methanol extraction of kola nuts by cold maceration showed that C. nitida had significantly lower total phenolic, flavonoid, and tannin contents than G. kola Heckel (TPCs: 1815.38±125.90 µg GAE; TFCs: 385.80±37.24 µg QE; and TTCs: 2643.75±36.08 µg TAE/g sample). 2.2-diphenyl-2-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays showed that G. kola Heckel (IC50 = 133.70 ± 0.11 µg/mL) was more effective than C. nitida (IC50 = 226.70 ± 0.21 µg/mL) at the 0.05 level. Studies on anti-inflammation found similar effects for G. kola Heckel and C. nitida (antiproteinase activity IC50 = 162.90 and 223.60 µg/mL; albumin denaturation: IC50 = 155.10 and 347.20 µg/mL; and membrane stabilization: IC50 = 183.50 and 271.70 µg/mL). Thus, it is proposed here that G. kola Heckel, in comparison to C. nitida, may be an acceptable source of energy, an antioxidant, and an anti-inflammatory agent in the nutraceutical and pharmaceutical sectors for the benefit of humans.